Revision of Ogdoecosta Spaeth 1909 with description of Ogdoecosta paraflavomaculata López-Pérez, sp. nov. (Coleoptera: Chrysomelidae: Cassidinae: Mesomphaliini) - López-Pérez, Sara; Zaragoza-Caballero, Santiago; Chaboo, Caroline S. (Zootaxa, 2016)
The tortoise beetle genus Ogdoecosta Spaeth 1909 is revised and an illustrated key to 12 species is provided, based on a morphological analysis of all species. All the known species are redescribed and one new species, Ogdoecosta paraflavomaculata López-Pérez sp. nov., is described from Belize and México. Lectotypes are designated for O. omissa Dohrn 1880, O. epilachnoides (Champion 1893), O. fasciata (Boheman 1856), O. flavomaculata (Champion 1893), O. mexicana (Champion 1893 and O. obliterata (Champion 1893). The distribution ranges for O. biannularis (Boheman 1854), O. catenulata (Boheman 1854), O. decemstillata (Boheman 1856), O. epilachnoides, O. fasciata, O. guttifera, O. juvenca, and O. obliterata are extended within México. Ogdoecosta guttifera (Boheman) is a new record for Venezuela.